1976
DOI: 10.1111/j.1600-0528.1976.tb01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience as predictor for caries incidence

Abstract: The caries increment (filled surfaces) from the ages 7 to 15 years were compared in children with three or fewer (low prevalence group) or eight or more filled surfaces (high prevalence group) at the age of 8. The children participated in a fortnightly fluoride mouthrinsing program (10 ml of 0.2% NaF). Following 8 years of dental treatment and caries prophylaxis, the caries increments were 11.4 (s.d. = 7.7, n = 23 subjects) and 17.1 (s.d. = 9.6, n = 39 subjects) surfaces, i.e. significantly different (t = 2.37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 4 publications
0
25
0
1
Order By: Relevance
“…In other studies the clinical caries exatnination has been found to be a good predictor of caries activity (2,14) and the observed correlation between 5. mutans Table 7 Number of rum carious lesions during 2nd year of study in six groups. Four of them were given special preventive measures once or twice a month.…”
Section: Discussionmentioning
confidence: 90%
“…In other studies the clinical caries exatnination has been found to be a good predictor of caries activity (2,14) and the observed correlation between 5. mutans Table 7 Number of rum carious lesions during 2nd year of study in six groups. Four of them were given special preventive measures once or twice a month.…”
Section: Discussionmentioning
confidence: 90%
“…As early as 1933, a relationship was reported between the caries experience of the decidu ous dentition and the permanent first molars [Frenzel, 1933]. Later studies have confirmed the existence of a relationship between the caries experience in both dentitions [Bruszt, 1959;Hill et al, 1967;Mansbridge, 1967;Adler, 1968;Poulsen and Holm, 1980;Raadal et al, 1984], Several studies have also shown a relation ship between caries experience and caries increment in the permanent dentition [Koch, 1970;Sutcliffe, 1973;Birkeland et al, 1976;De Liefde, 1982], So far, none of these studies have offered reliable caries pre dictor tests. However, it has been reported that among the variety of screening tests, the DM F index has the best potential for predicting caries risk in children [Honkala et al, 1984;Bader et al, 1986].…”
Section: Introductionmentioning
confidence: 77%
“…The association between caries experience of the deciduous dentition and caries increment in the per manent dentition was not analysed by computing the coefficient of correlation according to previous stud ies [Mansbridge, 1967;Adler, 1968;Birkeland et al, 1976;Honkala et al, 1984], The coefficient of correla tion, indicating the strength of association, is namely of limited use to determine the potential of the asso ciation as a valuable predictor for caries activity. The purpose of the present study was to evaluate the po tential of the association as caries predictor, by dicho tomizing the population into true positives and nega tives and false positives and negatives.…”
Section: Discussionmentioning
confidence: 99%
“…All lesions in the permanent teeth requiring a filling were supposed to be treated. In time trend analyses the DMFS scores at age 13 were significantly related to the number of surfaces filled when criteria for inserting fillings corresponded to lesions at the amelodentinal junction ter agreement between the number of surfaces filled and the increment in DMFS in children with low compared to high caries incidence due to less replacement of fillings at low caries activity [Birkeland et al, 1976]. A 70% decrease in the number of surfaces filled has been shown to be equivalent to 50% reduction of DMFS at age 14 .…”
Section: Methodological Commentsmentioning
confidence: 92%